Predictors of Disease-Free and Overall Survival in Retroperitoneal Sarcomas: A Modern 16-Year Multi-Institutional Study from the United States Sarcoma Collaboration (USSC). (2nd June 2019) - Schwartz, Patrick B.; Vande Walle, Kara; Winslow, Emily R.; Ethun, Cecilia G.; Tran, Thuy B.; Poultsides, George; Tseng, Jennifer; Roggin, Kevin; Grignol, Valerie; Howard, John Harrison; Krasnick, Bradley A.; Fields, Ryan C.; et al.
Abstract : Background . Retroperitoneal sarcomas (RPS) comprise approximately 15% of all soft-tissue sarcomas and frequently associated with significant morbidity and as little as 30% 5-year survival. Here, we provide a large, contemporary, and multi-institutional experience to determine which tumor, patient, and treatment characteristics are associated with long-term outcomes in RPS. Methods . 571 patients with primary RPS were identified from the United States Sarcoma Collaboration (USSC). RPS patients who underwent resection from January 2000 to April 2016 were included with patient, tumor, and treatment-specific variables investigated as independent predictors of survival. Survival analyses for disease-free and overall survival were conducted using Kaplan–Meier and Cox proportional hazards model methods. Results . The study cohort was 55% female, with a median age of 58.9 years (IQR: 48.6–70.0). The most common tumor histiotypes were liposarcoma (34%) and leiomyosarcoma (28%). Median follow-up was 30.6 months (IQR: 11.2–60.4). Median disease-free survival was 35.3 months (95% CI: 27.6–43.0), with multivariate predictors of poorer disease-free survival including higher grade tumors, nodal-positive disease, and multivisceral resection. Median overall survival was 81.6 months (95% CI: 66.3–96.8). Multivariate predictors of shorter overall survival included higher grade tumors, nodal-positive and multifocal disease, systemic chemotherapy, and grossly positive margins ( R 2) following resection. Conclusions . The strongest predictors of disease-free and overall survival are tumor-specific characteristics, while surgical factors are less impactful. Nonsurgical therapies are not associated with improved outcomes despite persistent interest and utilization. Complete macroscopic resection ( R 0/ R 1) remains a persistent potentially modifiable risk factor associated with improved overall survival in patients with retroperitoneal sarcomas.